(Des)encarceramento sociolinguístico de subalternizados presos da Unidade Prisional de São Luís de Montes Belos – Goiás - Tavares, Amanda Moreira (2019)
This research is a decolonial multisituated ethnographic study (REZENDE, 2017), based on written sociolinguistic practices of prisoners, who are in the process of "resocialization" in the Prison Unit of São Luís de Montes Belos, Goiás. are the problematization of a sociolinguistic question that emerges in the prison context, which is, at the same time, the imprisonment of the voices of the individuals arrested by the control of the speech and the disembarrassment of their voices, by the writing, that is an instance of power of the language; and evidence a shaving (FREITAS, 2016) in the system of sociolinguistic power, which is the possibility that the prisoners have to write to the district judge. The arrested person, in this work, is considered as subalternized (SPIVAK, 2010), which is to be subject to various practices of inferiorization, marginalization and silencing; and, therefore, in this discussion, is viewed from the perspective of critical interculturality. Society declares the prisoner to be an inferiorized being and, in this way, institutes his social erasure. There is a construction of the silencing of the speeches that may occur in this space, thus, in addition to the physical imprisonment, the sociolinguistic imprisonment of the arrested person. Any manifestation that distinguishes the prisoner from the others will share in his condition, also of subalternized, the exclusions proper to an oppressive system. To paraphrase Spivak (2010), we ask: Can the prisoner talk? The most immediate answer we have available is a resounding "no", it can not! Even knowing the intersubjective policies within prisons, where some prisoners hold all power, often overcoming state power itself, the prisoner can not speak. It is not only your body that is imprisoned, your voice is too! To be imprisoned in Brazil is to be in full conflict with the world around you. Brazil is undoubtedly a country of innumerable social inequalities, which violates the person in its spaces of culturalization. The prison is sanitized, silent, bodies are tamed and voices are silenced. In the midst of all this context of stigmatization and inferiorization, there is a shake that is highlighted in this research as results, when presenting the texts written by the prisoners coparticipants of the research and evidence the voicelessness of writing, which occurs despite the norm and performs a access to the judiciary even if it does not conform to linguistic standards.